Base excision repair is efficient in cells lacking poly(ADP-ribose) polymerase 1 - Vodenicharov, Momchil D. (Oxford University Press, 2000)
Poly(ADP-ribose) polymerase 1 (PARP-1) is a nuclear enzyme that is activated by binding to DNA breaks induced by ionizing radiation or through repair of altered bases in DNA by base excision repair. Mice lacking PARP-1 and, in certain cases, the cells derived from these mice exhibit hypersensitivity to ionizing radiation and alkylating agents. In this study we investigated base excision repair in cells lacking PARP-1 in order to elucidate whether their augmented sensitivity to DNA damaging agents is due to an impairment of the base excision repair pathway. Extracts prepared from wild-type cells or cells lacking PARP-1 were similar in their ability to repair plasmid DNA damaged by either X-rays (single-strand DNA breaks) or by N-methyl-N′-nitro-N-nitrosoguanidine (methylated bases). In addition, we demonstrated in vivo that PARP-1-deficient cells treated with N-methyl-N′-nitro-N-nitrosoguanidine repaired their genomic DNA as efficiently as wild-type cells. Therefore, we conclude that cells lacking PARP-1 have a normal capacity to repair single-strand DNA breaks inflicted by X-irradiation or breaks formed during the repair of modified bases. We propose that the hypersensitivity of PARP-1 null mutant cells to γ-irradiation and alkylating agents is not directly due to a defect in DNA repair itself, but rather results from greatly reduced poly(ADP-ribose) formation during base excision repair in these cells.